Unmanned : Drone Warfare and Global Security - Rogers, Ann and Hill, John (London Pluto Press, 2014)
Shows how unmanned systems are changing not simply how wars are fought, but the meaning of conflict itself.
Include Index and Bibliography
Keywords: Drone aircraft -- Security, International -- War--Moral and ethical aspects